2001
DOI: 10.1080/13639080120086157
|View full text |Cite
|
Sign up to set email alerts
|

Part-time Work and Full-time Education in The UK: The emergence of a curriculum and policy issue

Abstract: The 1990s have seen a burgeoning international, national and local literature on the significance of part-time work for those in full-time education. In this article, we trace the development of different strands of research in this area over the last decade. In common with other writers, we attribute the increased interest in the phenomenon of part-time work among full-time learners to changes in the youth labour market allied to rising levels of post-16 participation. Using evidence from three recent studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 4 publications
1
41
0
4
Order By: Relevance
“…Broadbridge and Swanson, 2005;Callender and Kemp, 2000) as well as other European countries (Hodgson and Spours, 2001). A majority of the sixth-formers in Elsheikh and Leney's (2002) research had a part-time job and, the authors argue, part-time working was an embedded part of their culture.…”
Section: Patterns Of Participationmentioning
confidence: 99%
See 2 more Smart Citations
“…Broadbridge and Swanson, 2005;Callender and Kemp, 2000) as well as other European countries (Hodgson and Spours, 2001). A majority of the sixth-formers in Elsheikh and Leney's (2002) research had a part-time job and, the authors argue, part-time working was an embedded part of their culture.…”
Section: Patterns Of Participationmentioning
confidence: 99%
“…A majority of the sixth-formers in Elsheikh and Leney's (2002) research had a part-time job and, the authors argue, part-time working was an embedded part of their culture. In the three studies discussed by Hodgson and Spours (2001) (Canny, 2002); continued economic growth, particularly in the service sector; new expensive objects of youth consumption; and the increased likelihood of incurring debt at university (Hodgson and Spours, 2001). In theorising these trends, du Bois Reymond (1998) has suggested that the tendency to combine work and learning (alongside a similar tendency to combine work and leisure time) has resulted in increasingly more complex concepts of life -which have gained wide cultural acceptance.…”
Section: Patterns Of Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the literature remains inconclusive, and Green and Jacques (2001) found no relationship between part-time work and students' academic performance. In the UK, Ford et al (1995) and Hodgson & Spours (2001) both accept that individuals will manage the balance of work and study differently, with some managing their time effectively while others struggle to cope with the demands of both.…”
Section: The Effect Of Part-time Work On Academic Studiesmentioning
confidence: 99%
“…Evans et al, 2014, Ford et al, 1995, Richardson et al, 2009), few have actually followed this up with finding out from students who do not work part-time, the reasons that underpin this decision (see for example, Hodgson and Spours, 2001). In this study, we asked students who do not work part-time, why they do not.…”
Section: Resultsmentioning
confidence: 99%